Immune mechanisms in cerebral ischemic tolerance - Garcia-Bonilla, Lidia; Benakis, Corinne; Moore, Jamie; Iadecola, Costantino; Anrather, Josef (Frontiers in Neuroscience, 2014)
Stressor-induced tolerance is a central mechanism in the response of bacteria, plants, and animals to potentially harmful environmental challenges. This response is characterized by immediate changes in cellular metabolism and by the delayed transcriptional activation or inhibition of genetic programs that are not generally stressor specific (cross-tolerance). These programs are aimed at countering the deleterious effects of the stressor. While induction of this response (preconditioning) can be established at the cellular level, activation of systemic networks is essential for the protection to occur throughout the organs of the body. This is best signified by the phenomenon of remote ischemic preconditioning, whereby application of ischemic stress to one tissue or organ induces ischemic tolerance in remote organs through humoral, cellular and neural signaling. The immune system is an essential component in cerebral ischemic tolerance acting simultaneously both as mediator and target. This dichotomy is based on the fact that activation of inflammatory pathways is necessary to establish ischemic tolerance and that ischemic tolerance can be, in part, attributed to a subdued immune activation after index ischemia. Here we describe the components of the immune system required for induction of ischemic tolerance and review the mechanisms by which a reprogrammed immune response contributes to the neuroprotection observed after preconditioning. Learning how local and systemic immune factors participate in endogenous neuroprotection could lead to the development of new stroke therapies.